The Digital Humanities Imperative: An Archival Response - MacDougall, Pauleena; Wynn, Katrina (Maine Policy Review, 2015)
The authors offer a look at how as archivists at the Maine Folklife Center they are using new digital tools to both preserve historical resources and improve public access to them.
Keywords: digital humanities; archives; Maine Folklife Center